HYDROCHEMICAL AND RADIOMETRIC STUDY OF GROUNDWATERS FROM SERRA NEGRA SPA, SÃO PAULO STATE, BRAZIL - Avona, Pietro D. [UNESP]; Bonotto, Daniel M. [UNESP] (Acadlore Publishing Services Limited, 2022)
This paper presents a novel hydrochemical and radiometric data of groundwater sampled from Serra Negra spa town, São Paulo State, Brazil. Every year, many visitors travel to the municipality, thus, recurrent analyses are recommended and necessary, as the local water is heavily consumed. However, gaps exist in this regard, especially for the groundwater selected for sampling in this paper, since there is no analytical data on its chemical composition. The results obtained were compared with the drinking water standards in relation to the analyzed parameters. The radioactivity of all analyzed samples was below the values established by the World Health Organization of 0.5 and 1 Bq. L−1 for gross alpha and beta activities, respectively. In general, the hydrochemical parameters analyzed did not exceed the reference limits established by Brazilian and international legislation, with the exception of pH for one water sample and nitrate for another. The use of Pearson’s correlation coefficient reinforced the proportionality between electrical conductivity and dissolved salts. In the chemical aspect, the dominant anion in the waters was bicarbonate, agreeing with the observed pH, while the predominant cation was sodium, possibly suggesting a slightly more evolved hydrogeochemical context. Although the Brazilian legislation does not mention a reference value for the ingestion of silicon in water, in this paper some comments were made about its presence in the analyzed groundwaters.
Keywords: hydrochemistry; potability; radioactivity; Serra Negra spa